а) {4х + y = 10; х + 3y = - 3; - выразим в первом уравнении у через х;y = 10 - 4x; - подставим во второе уравнение вместо у выражение (10 - 4х);x + 3(10 - 4x) = - 3;x + 30 - 12x = - 3;- 11x + 30 = - 3;- 11x = - 3 - 30;- 11x = - 33;x = - 33 : (- 11);x = 3;y = 10 - 4 * 3 = 10 - 12 = - 2.Ответ. (3; - 2)б) {5х + 2y = 15; 8х + 3y = - 1; - выразим в первом уравнении у через х;2y = 15 - 5x;y = (15 - 5x) : 2;y = 7,5 - 2,5x; - подставим во второе уравнение вместо у выражение (7,5 - 2,5x);8x + 3(7,5 - 2,5x) = - 1;8x + 22,5 - 7,5x = - 1;0,5x + 22,5 = - 1;0,5x = - 1 - 22,5;0,5x = - 23,5;x = - 23,5 : 0,5;x = - 47;y = 7,5 - 2,5 * (- 47) = 7,5 + 117,5 = 125.Ответ. (- 47; 125)